Occupational accidental injury deaths in Tokyo and Chiba prefectures, Japan: A 10‐year study (2011–2020) of forensic institute evaluations - Yamaguchi, Rutsuko; Makino, Yohsuke; Torimitsu, Suguru; Inokuchi, Go; Chiba, Fumiko; Yoshida, Maiko; Tsuneya, Shigeki; Oya, Yukiko; Yajima, Daisuke; Iwase, Hirotaro (Journal of Forensic Sciences, 2023)
Occupational accidental injury deaths (OAIDs) are a major social problem, and the analysis of individual cases is important for developing injury prevention measures. In this study, OAIDs with autopsies performed at forensic facilities in the metropolitan area of Japan (Tokyo and Chiba prefectures) from 2011 to 2020 were reviewed. The epidemiological characteristics of these OAIDs (n = 136), which accounted for 13.5% of OAIDs reported in the region during the study period, were compared with those of non‐occupational accidental injury deaths (non‐OAID) cases (n = 3926). Among OAID cases, 134 (98.5%) were men and 13 (9.6%) were foreign‐born workers, which was significantly more than in non‐OAID cases (p < 0.001, respectively). OAIDs were most frequent in construction (39.0%) followed by the manufacturing category (21.3%). The percentage of OAIDs in workers aged 65 and over showed an increasing trend. Most accidents occurred just after the start of work or just before the workday ended, as well as during the peak months of the year. The most common type of accident was fall/crash from a height (25.0%), and the most common injury site was the chest; none of these cases were confirmed to have been wearing a safety belt properly. Among foreign‐born workers, the most common type of accident was caught in/between. As the working population is expected to change in the future, and an increase in the number of older adults and foreign workers is expected, it is necessary to take preventive measures such as improving the work environment based on ergonomics and providing safety education.